Airborne Wind Energy Systems: Modelling, Simulation and Trajectory Control - Gonçalo Barros da Silva (2018)
In this dissertation, we address the generation of electrical power using Airborne Wind Energy Systems, comprising a kite connected through a tether to a generator on the ground. We do simulations of the kite model, both in 2D and 3D. Then we design a controller to steer the kite to follow a pre-defined periodic path, which includes a production mode, a tether retrieval mode, and a safe mode capable of handling wind gusts. Finally, we desing a controller based on a nonlinear guidance logic for trajectory tracking and compare the results.